Amaranthus – Cultivo de importancia Económica, investigaciones actuales 2018-2022. análisis bibliométrico. - Diaz Cajamarca, Brayan Fernando (2022)
Into current work, it was made a bibliographical research, using the keywords, Amaranth, Amaranthus, for fulfilling the raised topic, it was estableshed the following general aim: to identify the main made researches on the amaranth crop in the 2018-2022 years, with the Google Scholar platform use and the SCOPUS database, this aim was derived specific aims with activities that consisted of analyzing the scientific production with the Harzing's Publish or Perish software using got metadata from Google Scholar, as well as, in the Scopus Database, further, it was proposed to analyze the got data about the SCOPUS scientific production, in terms, documents by year, documents by author, documents by affiliation, documents by thematic area, documents by funding sponsor and document type and, finally, it was proposed to establish the authorship possible networks on the amaranth crop with the VOSviewer program use, since the results got, it can identify that when using the Harzing's Publish or Perish software with the got metadata from Google Scholar and the keyword Amaranthus, showed 1000 documents, with 8039 citations, 2009.75 citations an index per year, 8.04 citations per document, 3.66 authors per article, a 37 index-h, with a 57 index, while using the keyword Amaranth, it was got 373 documents, with a 230 citations index, 57.50 citations per year, 0.62 citations per document, 2.03 authors per article, a 5 index h and with an 8 index g. While into SCOPUS with the keyword Amaranthus, it was found 2000 documents, with a 11426 citations index, 2856.50 citations per year, 5.71 citations per document, 5.01 authors per article, a 39-index h and with 56 index g. when using the keyword Amaranth, it was found 18 documents, with a 5 citations index, 1.25 citations per year, 0.28 citations per document, 4.50 authors per article, into 1 index h and with a 1 index g. Likewise, it could been determined, what it was the largest documents published number into SCOPUS with the raised topics was in the 2021 with 557 documents; the researcher with the contributions highest number was Norsworthy, J.K. With 36 published works, from institutions, which have published the most on the Amaranthus topic, it stood out the Arkansas University with 54 documents, the topic with the contributions highest percentage was Agriculture and Biological Sciences with 39.4%, the entity, which has provided significant economic resources for project management and publication has been the National Natural Science Foundation from China, the document type that has been published the most is unpublished and original scientific articles with 84.4 %. And, finally, with the VOSviewer software support, it has been possible to identify 7 authorship networks, made up by 39 authors, who have published more than 10 scientific articles. From the got data, it is recommended bibliographic reviews, before generating projects, writing articles, books, among other academic contributions, it is also necessary to promote the bibliographic managers use, such as Mendeley, as well as new software, such as Harzing's Publish or Perish and VOSviewer to perform bibliometric analysis.